Ladder‐Type Perylene Diimides Linked by Pyrene Bridges at Bay Area. Issue 2 (16th February 2016) - Ren, Tianfei; Shen, Xiaoxiao; Han, Lingui; Bai, Libin; Zhao, Hongchi; Wu, Yonggang; Wang, Haijun; Ba, Xinwu
Abstract: A series of ladder‐type pyrene‐fused perylene diimides were designed and synthesized. To prepare the appropriate precursors, bromo‐perylene diimides and Bpin‐pyrene materials need to be coupled via Suzuki reaction. Whereas the Pd(PPh3 )4 ‐catalyzed Suzuki reaction by heating was in low efficiency for the preparation of some precursors. For better yield, a microwave‐assisted Suzuki coupling reaction was used to prepare precursors. As expected, most of precursors were synthesized successfuly, however, the longest precursor was very difficult to obtain via Pd(PPh3 )4 ‐catalyzed Suzuki reaction even under microwave‐assisted. When 1, 1′‐bis(diphenylphosphino)ferrocene palladium dichloride (Pd(dppf)Cl2 ) was empolyed as catalyst for Suzuki reaction, the longest precursor could be obtained in better yield. Subsequently the oxidative cyclization could smoothly proceed to form ladder structure with common catalyst 2, 3‐dichloro‐5, 5‐dicyano‐1, 4‐benzoquinone /BF3 Et2 O or FeCl3, and all ladder‐type perylene diimides exhibited high fluorescence quantum yield and bright red emission in solution, therefore could be good candidates for red emitting materials. Abstract : A series of ladder‐type pyrene‐fused perylene diimides were synthesized. In the process a microwave‐assisted Suzuki coupling reaction and selective catalyst Pd(dppf)Cl2 were used for preparing the appropriate precursors, subsequently the cyclization could smoothly proceed to form ladder structure with common catalyst FeCl3 .